2010
DOI: 10.1161/circresaha.109.211417
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Nrf3 in Smooth Muscle Cell Differentiation From Stem Cells

Abstract: Rationale: Nuclear factor erythroid 2-related factor (Nrf)3, a member of the cap 'N' collar family of transcription factors that bind to the DNA-antioxidant responsive elements, is involved in reactive oxygen species balancing and in muscle precursor migration during early embryo development. Objective: To investigate the functional role of Nrf3 in smooth muscle cell (SMC) differentiation in vitro and in vivo. Methods and Results: Nrf3 was upregulated significantly following 1 to 8 days of SMC differentiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 42 publications
3
76
0
Order By: Relevance
“…Murine ESCs were induced to differentiate towards SMCs as described previously (Supplementary Figure S1). [11][12][13][14] miRNA microarrays analysis was conducted to identify potential miRNA candidates for SMC differentiation, and the data revealed that miR-290 family members, the reported ESC-specific miRNA cluster, 15 were dramatically downregulated upon differentiation (Supplementary Table S1). Conversely, muscle differentiation-related miRNAs (miR-143/145/133) were increased in our SMC differentiation model, while SMC proliferation-related miR-21 was undetectable at early stage but dramatically increased at late stage of SMC differentiation, indicating that some miRNAs may initiate SMC differentiation, whereas others may have important roles in the late stage of SMC differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine ESCs were induced to differentiate towards SMCs as described previously (Supplementary Figure S1). [11][12][13][14] miRNA microarrays analysis was conducted to identify potential miRNA candidates for SMC differentiation, and the data revealed that miR-290 family members, the reported ESC-specific miRNA cluster, 15 were dramatically downregulated upon differentiation (Supplementary Table S1). Conversely, muscle differentiation-related miRNAs (miR-143/145/133) were increased in our SMC differentiation model, while SMC proliferation-related miR-21 was undetectable at early stage but dramatically increased at late stage of SMC differentiation, indicating that some miRNAs may initiate SMC differentiation, whereas others may have important roles in the late stage of SMC differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed protocols for mouse ESCs (mESCs) (ES-D3 cell line, CRL-1934; ATCC, Manassas, VA, USA) culture and SMC differentiation were described in our previous studies. [11][12][13][14]17,22,34,43,44 The Shef-1, 2, 3, 6, and 7 human ESC lines were obtained from the United Kingdom Stem Cell Bank (UKSCB, Hertfordshire, UK) and maintained in our Laboratory as described in our previous study. 18 Briefly, undifferentiated ESCs were dissociated into single cells and seeded onto collagen I/IV (5 μg/ml)-coated flasks or plates in differentiation medium (DM, MEM alpha medium (Gibco, Carlsbad, CA, USA) supplemented with 10% FBS, 0.05 mM 2-mercaptoethanol, 100 U/ml penicillin, and 100 μg/ml streptomycin) for 0-9 days prior to further treatment.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%
“…Cell Culture and SMC Differentiation-Detailed protocols for mouse ES cell (ES-D3 cell line, CRL-1934; ATCC, Manassas, VA) culture and SMC differentiation were described in our previous studies (2)(3)(4)(5)(6)(7)(8). For SMC differentiation, undifferentiated ES cells were seeded on mouse collagen IV (5 g/ml)-coated flasks or plates in differentiation medium (DM), ␣-minimal essential medium (Invitrogen) supplemented with 10% FBS, 0.05 mM ␤-mercaptoethanol, 100 units/ml penicillin, and 100 g/ml streptomycin for 3-7 days prior to further treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Other Procedures-Experiments of nucleofection, siRNA experiments, indirect immunofluorescent staining for cells, and real time quantitative PCRs (RT-qPCR) were performed according to the standard procedures as described previously (2)(3)(4)(5)(6)(7)(8). Whole mount immunohistochemistry and in situ hybridization were carried out as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation